What are the problem-solving skills among international postgraduate students at the Universiti Sains Malaysia according to heppner's assessment? - Ewies, Mahmoud Ghazi; Che Ahmad, Aznan; Hamzah, Aswati (Jurnal Pendidikan Bitara UPSI, 2021)
This research paper aims to assess the problem-solving ability of international postgraduate students at Sains Malaysia University. To achieve the research goal, the researchers used Heppner's assessment to reveal the ability to solve problems. The assessment contains five dimensions: General attitude, Identification of the Problem, Generating alternatives, Making a decision, and Assessment. To reach the study result, the researchers used the Statistical Package for Social Sciences (SPSS) version 25. After ensuring the tools' reliability and validity, the researchers collected data from the randomly selected sample, and the number of students participating in the assessment reached 159 students. The researchers used the ANOVA test to get the findings. The study results showed statistical differences in students' abilities in problem-solving skills, where the students' excellence was in the skill of problem identification. The decision-making skill came in second place, followed by dealing with the problem, generating alternative solutions, and evaluating solutions. Based on the study results, the researchers recommended paying attention to problem-solving capabilities, especially assessing proposed solutions to solve problems and enhance and develop other skills.